The Efektifitas Penulisan Dokumentasi Triase Emergency Severity Index (ESI) Dengan Canada Triage Acuity Scale (CTAS) Terhadap Ketepatan Prioritas Triase Pasien Oleh Mahasiswa Ners STIKES Cahaya Bangsa di IGD RSUD Ulin Banjarmasin - Doni Wibowo (HB PRESS, 2020)
Nursing education is the end of the nursing profession education process which will carry out its work as a nurse profession in the health care services. Emergency department (IGD) is one of the main entrances of inpatients, so that patient visits in the ER is quite high, and it cause the overcrowded. It needs a triage system and documentation based on evidence to increase success in the management of patients with emergency conditions. The purpose of this study is to study the effectiveness of the Emergency Severity Index triage discussed with the Canadian Triage Acuity Scale on the accuracy of patient triage priorities. This study use the Quasi Experimental method using the Mann Whitney test. The sampling technique uses accidental sampling with a total of 50 Emergency Severity Index triage documentation samples and 50 Canada Triage Acuity Scale documentation samples. The results showed accuracy in determining the priority of triage in 46 tragedy Emergency Severity Index (92%) and 38 documentation of Canadian Triage Acuity Scale (76%). There is a difference in the accuracy of the triage priorities of patients between the triage documentation of the Emergency Severity Index and the Canada Triage Acuity Scale with a p value of 0.030. It is time for the Emergency Department (IGD) to implement evidence-based triage systems and documentation by adopting or developing scientifically tested triage systems and documentation.